2014
DOI: 10.1002/etc.2519
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity of treated municipal wastewater effluent on Bombina orientalis (Amphibia: Anura) embryos

Abstract: Amphibian populations have been decreasing in urban freshwater systems in Korea. To elucidate the biological safety of treated wastewater effluent (TWE) in the Tancheon basin, the capital area of Korea, a 7-d-exposure Bombina orientalis embryo developmental toxicity assay was examined during the breeding season. In March, there were no significant differences in embryonic survival or malformation among the water samples. In July, following monsoon precipitation, embryonic lethality in TWE was significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Furthermore, based on the presence of morphological abnormalities close to cities (Kang et al, 2016), we could have expected individuals with additional or missing limbs, which was not the case. We expect the hatching and development rate of individuals breeding in the pond to be significantly lower, as Park et al (2014) reported the failure of embryonic development in polluted waters. Finally, we hypothesise that calling individuals found in 2016 were in the plastic bags as they would have provided a warmer environment, and may have potentially provided call amplifiers.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, based on the presence of morphological abnormalities close to cities (Kang et al, 2016), we could have expected individuals with additional or missing limbs, which was not the case. We expect the hatching and development rate of individuals breeding in the pond to be significantly lower, as Park et al (2014) reported the failure of embryonic development in polluted waters. Finally, we hypothesise that calling individuals found in 2016 were in the plastic bags as they would have provided a warmer environment, and may have potentially provided call amplifiers.…”
Section: Discussionmentioning
confidence: 93%
“…The mostly terrestrial variety "sylvatica" is usually associated with forest habitats and never present in open wetlands further than 200 m from the forest border (Kuzmin & Maslova, 2005), while the aquatic variety "praticola" is only recorded in sedge and reed meadows when associated with grasslands (Korotkov, 1972). The species is known to be sensitive to environmental pollutants due to abnormal development when close to human activities (Kang et al, 2016) and failure of embryonic development in polluted waters (Park et al, 2014). The species is common in forested zones around Vladivostok, Russia (Kuzmin & Maslova, 2005), but was not expected to be present within the city due to habitat disconnection and heavy pollution (Vshivkova et al, 2014 ;Vshivkova, 2016;Maslova et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of dissolved substances and toxicity of wastewaters increase during the periods of plentiful rainfall and were demonstrated with bacterial lux-biosensors and toxic influence on amphibian larvae (Palma et al 2010;Park et al 2014).…”
Section: Resultsmentioning
confidence: 98%
“…Although we do not know the quality of water in our study sites, many creeks are in close proximity with potential pollution sources which may contain human generated chemicals, such as pyrethroid insecticides (tourist attractions, pensions, and camping sites), agricultural chemicals (agricultural fields, orchards), or effluent (dwelling houses), which can affect frog development (Berrill et al 1993, Mann et al 2009, Park et al 2014). In the study by Park et al (2014), B. orientalis tadpole abnormality rates increased in municipal effluent water that was not fully treated, with a mean abnormality rate of 20%, compared to those raised in unpolluted upstream water (mean abnormality rate, 3%). They also showed that rate of abnormalities was positively correlated with total water nitrogen, which has a detrimental effect on amphibian development (Rouse et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Bombina orientalis (Bombinatoridae) provides a good opportunity to study the relationship between human land use and abnormalities in amphibians inhabiting a lotic environment, because i) they are a common species found in both lentic and lotic environments such as most creeks and streams, ii) they are vulnerable against human generated pollutants for abnormalities to be developed under the pollutant conditions (Park et al 2010, Park et al 2014, and iii) many of the accessible streams and creeks are in close proximity with land used by humans such as agricultural fields, where pesticides and herbicides are often sprayed. Here, we studied the relationship between the degree of human activity and the incidence of abnormally developed frogs on wild populations of B. orientalis.…”
Section: Discussionmentioning
confidence: 99%